Crash fears and stock market effects : evidence from web searches and printed news articles - Nikkinen, Jussi; Peltomäki, Jarkko (Taylor & Francis, 2019)
The authors studied the complex relationship between information supply and demand using newspaper articles and web searches that reflect investors’ crash fears. They report that more web searches lead to more news, whereas more news does not have that effect on web search in the future. The authors show also that web searches have an immediate effect on stock market returns and the VIX implied volatility, whereas the effect of news articles lasts longer, up to 11 weeks. The results suggest collectively that the web searches related to market crashes lead both the printed news stories about market crashes.
Keywords: crash fear; volatility; information supply and demand; web search; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|